Stavka in druge industrijske akcije - Novak, Janez (Delavci in delodajalci, 2012)
The purpose of the article is to present different legal forms of industrial ations through analysis of legal regulations. The author first determines the general term 'industrial action', then the general/typical term 'strike' and finally other legal forms of strike which differ from the 'standard' form. In conclusion he examines other industrial actions, including that of lockout, asthe employer's main counterweight to the strike.
Keywords: delovni spor; stavke; zaposleni